2023
DOI: 10.3390/buildings13092245
|View full text |Cite
|
Sign up to set email alerts
|

Bias in the Estimation of Seismic Risk for Municipal Building Stocks Due to Limited Data

Anže Babič,
Jure Žižmond,
Matjaž Dolšek

Abstract: This study investigated the effect of the building data knowledge level on seismic risk estimation for municipal building stocks, focusing on identifying the characteristics that influence loss estimation bias. Fifteen municipalities in two Slovenian regions were analysed using twelve building data knowledge levels, defined by combining different knowledge levels about building location and floor area. The knowledge levels ranged from those using data aggregated at the municipality level to those using buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The intensity measure selected for the model was the PGA for the rock-equivalent outcrop motion, and its values were determined at the centre of each municipality for six return periods (50, 101, 476, 976, 2500, and 5000 years). A previous study showed that considering the same hazard for all buildings in a municipality does not significantly affect the risk estimation (Babič et al 2023). Figure 4 shows the hazard map for the return period of 976 years, representing the PGA value at the centroid of each municipality (as shown in the BORIS platform).…”
Section: 2mentioning
confidence: 99%
“…The intensity measure selected for the model was the PGA for the rock-equivalent outcrop motion, and its values were determined at the centre of each municipality for six return periods (50, 101, 476, 976, 2500, and 5000 years). A previous study showed that considering the same hazard for all buildings in a municipality does not significantly affect the risk estimation (Babič et al 2023). Figure 4 shows the hazard map for the return period of 976 years, representing the PGA value at the centroid of each municipality (as shown in the BORIS platform).…”
Section: 2mentioning
confidence: 99%